(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This condition certainly creates tight competition among coffee shop business actors. The number of coffee shops certainly influences consumer purchasing decisions at each coffee shop because consumers have many choices. The purpose of this research is to determine the influence of Electronic Word of Mouth, Servicescape, and Store Atmosphere on purchasing decisions. This research was conducted at Tan Panama Coffee in Denpasar City. The population in this study was 70,691 consumers of Tan Panama Coffee. The sample size was determined using the Slovin formula so that the sample was determined to be 100 consumers. Data testing was carried out using the multiple linear regression method. The results of the partial significance test prove that Electronic Word of Mouth, Servicescape and Store are able to have a positive and significant influence on purchasing decisions. Suggestions that can be given include adjusting the recipe so that the taste is consistent, providing more indoor space, and redesigning the building so that it is unique.